Characteristics of Companies with Numerous Disclosed Material Weaknesses in Internal Control over Financial Reporting - Anttila, Linda (My University, 2015)
Since the massive accounting scandals of the early 2000s and the enactment of the Sarbanes-Oxley Act of 2002 (SOX) the management of companies that are listed in the U.S. have been obligated to release an assessment of the effectiveness of the company’s internal control over financial reporting (ICFR). With respect to the internal control assessment made by the management, each registered public accounting firm that issues the audit report for the company must attest to, and report on, the management’s assessment. The purpose of this study is to examine the special characteristics of companies that have disclosed numerous material weaknesses (MWs) in ICFR. Previous studies related to the topic have concentrated mainly on the determinants of MWs, or the companies reporting deficiencies in ICFR in general. However, to my knowledge, there are no prior studies that have focused especially on the companies disclosing many different kinds of MWs in ICFR. Hence, this is a groundbreaking study, and the findings help understanding what kind of firm characteristics may expose company to extensive issues with ICFR. The sample gathered for the analysis of characteristics of companies disclosing numerous MWs in ICFR consist of 431 companies and the research period covers the years 2005–2008. The internal control reporting data is gathered from the Audit Analytic database, and the companies that have disclosed at least one MW in ICFR and have the required SOX reporting data available from all the years covered by the research period are included in the sample. I use panel data analysis – more precisely Fixed Effects model – in order to analyze the characteristics of companies disclosing numerous MWs in ICFR. The findings suggest that the number of disclosed MWs in ICFR is positively associated with company’s number of operational segments and rapid growth of sales. Further, I find that 26.9% of the variation in the number of disclosed MWs is due to company-specific effects.
Keywords: Internal control; Material weakness; Sarbanes-Oxley; fi=Laskentatoimi ja rahoitus|en=Accounting and Finance|; fi=Laskentatoimen ja tilintarkastuksen maisteriohjelma|en=Master's Programme in Accounting and Auditing|